Inversión extranjera directa y productividad laboral en la industria manufacturera regional - Erick Rangel González; Luis Fernando López Ornelas (Banco de México, 2021)
– Foreign Direct Investment (FDI) is often identified as a driver of economic growth, although there is no consensus on this topic in the international empirical evidence regarding its effect on labor productivity. This document analyzes the effects of Foreign Direct Investment on labor productivity in the manufacturing sector in Mexico during the 2007-2015 period by using panel data and federative entities as unit of analysis. The estimates are calculated by the generalized method of moments, which allows to consider for possible endogeneity problems. The results indicate a positive and statistically significant effect of FDI as a proportion of manufacturing GDP on the growth rate of labor productivity when the latter is estimated with the Manufacturing Labor Productivity Index published by INEGI. Similar results are found if growth in labor productivity is estimated by using manufacturing GDP per worker, although the latter have less statistical power in some specifications.
Keywords: J01; J24; Q29; R11; 330; Labor Productivity; Foreign Direct Investment; Manufacturing; Mexico